The analysis of means techniques - Karas, Shawky F (Journal of Experimental Education, 1968)
The theoretical basis for the Analysis of Means Technique is discussed. In addition, a simplified working procedure is outlined, step-by-step for an actual problem. The data for the problem are analyzed by the analysis of means techniques, which compares differences between means instead of population variances estimates. The data are also analyzed by the analysis of variance technique. The conclusions reached by both techniques are the same. The graphical representation of the ANOM is helpful in understanding data. The ANOM technique is usually used in conjunction with the analysis of variance, either as an initial analysis of data or to augment the analysis of variance. © Taylor & Francis Group, LLC.
Keywords: dept.psy